Comparison of enzyme immunoassay and culture for diagnosis of chlamydial conjunctivitis and respiratory infections in infants. - Hammerschlag, M R (1987)
The efficacy of Chlamydiazyme (Abbott Laboratories, North Chicago, Ill.) in detecting neonatal conjunctival and respiratory infections caused by Chlamydia trachomatis was determined by comparison of this enzyme immunoassay (EIA) with the method of isolation of chlamydiae in tissue culture. The sensitivity and specificity of Chlamydiazyme for detecting C. trachomatis in conjunctival specimens from infants with conjunctivitis were 98 and 94%, respectively. For nasopharyngeal infection in infants with conjunctivitis, the sensitivity and specificity were 87 and 92%, respectively. There were nine nasopharyngeal specimens that were Chlamydiazyme positive and culture negative. All of these specimens demonstrated the presence of typical fluorescing chlamydial elementary bodies when pellets of the original specimens were examined with a fluorescein-conjugated monoclonal antibody. When the EIA was performed on nasopharyngeal specimens from infants with suspected chlamydial pneumonia, 6 culture-positive and 10 culture-negative specimens were correctly identified.